Which ones are more important: characteristics or complexities? A study of the disclosure in local government financial reports - Purnama, Hari Purnama; Alfina, Putri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2019)
Local Government Financial Report (LGFR) is one form of local government transparency in financial reporting for a period. The study aims to determine the effect of characteristics as proxied by the assets and size of local government, and complexity as proxied by the number of LGFRs and size of Legislature on the extent of financial report disclosure of local government. The data employed in this study are Local Government Financial Reports from 9 Municipal Governments and 18 Regencial Governments in West Java for the period 2014-2017. The results of this study suggest that the asset and size of local government have a positive effect on the degree of financial report disclosure of local government. On the other hand, the number of LGFR and legislature size has no effect on financial report disclosure of local government.